ECOCRITICISM IN ALEXANDRA KLEEMAN’S SOMETHING NEW UNDER THE SUN - Intisar Rashid Khaleel (European Journal of Humanities and Educational Advancements, 2023)
Today’s world is significantly distinct from that of the past. With so much new technology and new ideas, it can be difficult to keep up with the changes. One thing that has remained constant, however, is the importance of understanding the environment and how our actions can affect it. Alexandra Kleeman’s Something New Under the Sun (2021) projects the way how humanity interacts with nature, and how our actions and attitudes can have an effect on the environment. She examines the importance of understanding our impact on the environment and how we should strive to live in harmony with nature. Through her characters, Kleeman conveys the message that nature can be a source of both beauty and destruction if we allow it. Kleeman occasionally employs more hyperrealism, breaking out from the scene at hand and sending the reader elsewhere completely. The details of the supposed catastrophe are not Kleeman’s objective in Something New Under the Sun. Though, she did envision some drastic measures that would be necessary to take. However, the main object in the novel appears to be how humanity reacts to terrifying, significant shifts, and how carelessness may outlive even the clearest signs of catastrophe